Remote Programming of Cochlear Implants. Issue 3 (March 2019) - Slager, Heidi K.; Jensen, Jamie; Kozlowski, Kristin; Teagle, Holly; Park, Lisa R.; Biever, Allison; Mears, Megan
Abstract : Objective: This study investigated the safety and efficacy of remote programming of cochlear implants. Study Design: Single-subject design Setting: Four North American clinical sites Patients: Forty cochlear implant recipients aged 12 years or older Intervention: Subjects had their cochlear implants programmed at a location that was remote from their audiologist using telecommunication with and without the support of a facilitator. Main Outcome Measures: Consonant-Nucleus-Consonant (CNC) word scores and the Speech, Spatial, and Qualities of Hearing Scale-C (SSQ-C) were compared using the subject's in-office MAP (program) and MAPs programmed remotely with and without the assistance of a facilitator. Additional subjective preference data were gathered from subjects and audiologists via questionnaires. Results: MAPs programmed via the three different models did not yield significantly different group mean CNC word scores. No device/procedure-related adverse events occurred. SSQ-C questionnaire results indicated that recipients received similar subjective benefit from familiar in-office, remote-facilitated, and remote-unassisted MAPs. Conclusions: Remote programming is an effective means of cochlear implant service delivery. The practice was approved by the FDA on November 17, 2017 supported by the results of this study.